2009
DOI: 10.1242/dev.041160
|View full text |Cite
|
Sign up to set email alerts
|

Conditional knockdown of Nanog induces apoptotic cell death in mouse migrating primordial germ cells

Abstract: The pluripotency factor Nanog is expressed in peri-implantation embryos and primordial germ cells (PGCs). Nanog-deficient mouse embryos die soon after implantation. To explore the function of Nanog in germ cells, Nanog RNA was conditionally knocked down in vivo by shRNA. Nanog shRNA transgenic (NRi-Tg) mice were generated through the formation of germline chimeras with NRi-Tg embryonic stem cells. In E12.5 Cre-induced ER-Cre/NRi-Tg and TNAP-Cre/NRi-Tg double-transgenic embryos, the number of alkaline phosphata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
101
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 52 publications
(69 reference statements)
9
101
0
Order By: Relevance
“…These experiments hence suggested a potential role of Nanog in the reprogramming process. However, an independent study using the in vivo knockdown approach of Nanog revealed a gradual loss of PGCs prior to the reprogramming step, supporting the notion that Nanog is involved in the maintenance of the germline [17].…”
Section: Towards the Epigenetic 'Ground State'mentioning
confidence: 79%
“…These experiments hence suggested a potential role of Nanog in the reprogramming process. However, an independent study using the in vivo knockdown approach of Nanog revealed a gradual loss of PGCs prior to the reprogramming step, supporting the notion that Nanog is involved in the maintenance of the germline [17].…”
Section: Towards the Epigenetic 'Ground State'mentioning
confidence: 79%
“…Conditional knockout of Oct4 or conditional knockdown of Nanog in migrating PGCs results in the death of PGCs by apoptosis, indicating the importance of these gene products in the maintenance of PGCs (Table 1) (Kehler et al 2004;Chambers et al 2007;Yamaguchi et al 2009). Hypoxia-inducible factor 2a (HIF2a), which has a function to directly up-regulate Oct4, is also critical in PGC specification and/or survival ( Fig.…”
Section: The Functions Of Pluripotency Genes In Pgcsmentioning
confidence: 99%
“…Single-cell expression analysis in Nanog-depleted PGCs at E10.5 indicated significant up-or downregulation of several genes, including the repression of Id1 and the PRC2 subunit Suz12. However, major transcriptional regulators of germ cell fate were similarly expressed between Nanog knockdown and control PGCs [25]. These data suggest that lack of Nanog expression causes the loss of PGCs by E12.5 as a result of progressive apoptotic cell death, rather than trans-differentiation to a somatic cell fate.…”
Section: Nanog Is Required For the Formation Of Naive Pluripotency Anmentioning
confidence: 75%
“…Deletion of Nanog in established ES cells however does not impair ES cell self-renewal, and upon re-introduction of these in development they are competent to efficiently contribute to all somatic lineages [8]. However, Nanog-deficient ES cells fail to contribute to the germ lineage beyond E11.5 [8,25].…”
Section: Nanog Is Required For the Formation Of Naive Pluripotency Anmentioning
confidence: 99%
See 1 more Smart Citation